Amyloid oligomers as on-pathway precursors or off-pathway competitors of fibrils - Muschol, Martin; Hoyer, Wolfgang (Frontiers in Molecular Biosciences, 2023)
Amyloid Diseases involve the growth of disease specific proteins into amyloid fibrils and their deposition in protein plaques. Amyloid fibril formation is typically preceded by oligomeric intermediates. Despite significant efforts, the specific role fibrils or oligomers play in the etiology of any given amyloid disease remains controversial. In neurodegenerative disease, though, amyloid oligomers are widely considered critical contributors to disease symptoms. Aside from oligomers as inevitable on-pathway precursors of fibril formation, there is significant evidence for off-pathway oligomer formation competing with fibril growth. The distinct mechanisms and pathways of oligomer formation directly affect our understanding under which conditions oligomers emerge in vivo, and whether their formation is directly coupled to, or distinct from, amyloid fibril formation. In this review, we will discuss the basic energy landscapes underlying the formation of on-pathway vs. off-pathway oligomers, their relation to the related amyloid aggregation kinetics, and their resulting implications for disease etiology. We will review evidence on how differences in the local environment of amyloid assembly can dramatically shift the relative preponderance of oligomers vs. fibrils. Finally, we will comment on gaps in our knowledge of oligomer assembly, of their structure, and on how to assess their relevance to disease etiology.